The Influence Of Digital Payment Usage Quick Response Code Indonesian Standard (Qris) And Menu Variety On Repurchase Interest In Hore Steak Magetan - Mafta Fiala Athalita; Nuruni Ika Kusuma Wrdani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Quick Response Indonesian Standard QRIS is the unification of various QRs from various Payment System Service Providers (PJSP) using the QR Code. Many are highly interested in QRIS payments because not only are they quick and efficient, but they also help minimize risk. Menu variety refers to the range of products and items sellers offer customers. Customers are keen on having a wide range of options on food menus because they desire a variety of choices in the food items provided. The research aims to find out the Influence of Digital Payment Usage Quick Response Code Indonesian Standard (QRIS) and Menu Variety on Repurchase Interest in Hore Steak Magetan. The population of this study is consumers of Hore Steak Magetan who are at least 17 years old and have a smartphone. The research employed a purposive sampling method using 110 samples. Data is analyzed using Smart PLS with outer and inner model methods. The findings indicated that the QRIS payment method had a positive and significant influence on repurchase interest, menu variety had a positive and significant influence on repurchase interest, and the QRIS payment method and menu Variety together had a positive and significant influence on repurchase interest.